2013
DOI: 10.3163/1536-5050.101.4.010
|View full text |Cite
|
Sign up to set email alerts
|

“You're just one of the group when you're embedded”: report from a mixed-method investigation of the research-embedded health librarian experience

Abstract: Given that research-embedded librarianship appears to be a distinct and growing subset of health librarianship, libraries, master's of library and information science programs, and professional associations will need to respond to the support and education needs of REHLs or risk losing them to the health research field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Moreover, unlike their academic counterparts, REHLs do not face the same time constraints frequently reported by academic librarians as barriers to participating in large review projects [5]. In a 2013 mixed-method study, REHLs reported "traditional" library tasks as the least commonly performed or never performed out of thirteen categories of research librarian tasks, while the most commonly performed involved "informationrelated elements of the research process" [6]. The movement of REHLs away from traditional library management and service support has created opportunities for librarians to expand their roles beyond expert searching to include information and workflow management support [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, unlike their academic counterparts, REHLs do not face the same time constraints frequently reported by academic librarians as barriers to participating in large review projects [5]. In a 2013 mixed-method study, REHLs reported "traditional" library tasks as the least commonly performed or never performed out of thirteen categories of research librarian tasks, while the most commonly performed involved "informationrelated elements of the research process" [6]. The movement of REHLs away from traditional library management and service support has created opportunities for librarians to expand their roles beyond expert searching to include information and workflow management support [2].…”
Section: Introductionmentioning
confidence: 99%
“…The movement of REHLs away from traditional library management and service support has created opportunities for librarians to expand their roles beyond expert searching to include information and workflow management support [2]. Through the provision of customized, comprehensive information services, embedded librarians can open avenues for more prominent and active participation as members of the research team [6].…”
Section: Introductionmentioning
confidence: 99%
“…Some research libraries are responding to the challenge by moving beyond alignment with academic departments or schools to focus provision of indepth information advice at the more specialized and dynamic level of research groups and projects, particularly in the biomedical and health sciences area (Carlson & Kneale, 2011;Federer, 2013;Greyson & Surette, 2013). Another significant trend is the creation of specialist positions dedicated to research support, either exclusively or in addition to a subject librarian role (Bradbury & Weightman, 2010;Young & Lund, 2008), including positions coordinating support for graduate students (Covert-Vail & Collard, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…39 "There is great "value of ''belonging'' to the research team, being involved in projects from conception through to publication, and developing in-depth relationships." 63 "The researcher has relations of dependence with the host organisation, which might shape the type of research that is conducted and the dissemination of findings." …”
Section: Benefits Of the Embedded Researcher Methods Limitations Of Thmentioning
confidence: 99%
“…In an interactive perspective this technique equalises the power between the practitioners and researchers and allows the practitioners to provide research questions and play a vital role in providing and supporting solutions. 59,63 There are advantages of adapting the research to a particular healthcare environment. A successful Embedded Researcher is able to compromise because of their background and training which enables them to understand the path of clinical decision making.…”
Section: The Benefits Of the Embedded Researcher Techniquementioning
confidence: 99%